KUALITAS SUMBERDAYA MANUSIA PESISIR PANTAI DI KELURAHAN BUNAKEN KECAMATAN BUNAKEN KEPULAUAN KOTA MANADO - TAWARIS, DEISY NATALIA; RORONG, ARIE JUNUS; TULUSAN, FEMMY (Sam Ratulangi University, 2019)
Human resources is divided into two, namely, human resource macro is a resident of a country that has already entered the age of the work force, either not working or who are already working. While understanding the micro is the individual work and became a member of a company or institution and is commonly referred to as employees, workers, employees, workers, labor and others Nawawi (2003:37). Coastal communities need real activities that can build their economies without eliminating the culture and characteristics of coastal communities, the required form of community-based activities. This research uses descriptive qualitative approach method. This study describes the data obtained from the results of research on the quality of human resources the coast (study in the Bunaken island sub-district of Manado city). In qualitative research, data collection is done by observation, in-depth interviews and documentation. Based on research results drawn the conclusion that the quality of human resources viewed from three indicators categorized quite well. The quality of human resources in particular physical health fishing communities quite well seen from the community who care about their own health and are already providing health support facilities and infrastructure for the community. For the quality of intellectual (education andtraining) itself is also quite good because there's been an effort of the Government in the fulfillment of the educational infrastructure and facilities for the community as well as the already existing cooperation with the Fisheries Agency in empowering human resources especially fishing communities. The quality of human resources in terms of the spiritual quality of its own quite well seen from the daily life of fishing communities in the society and harmony between religious communities in compliance, and comply with the rules made by the Government, as well as the morale of the fishing communities in doing his job. So the Government in directing the village empowerment on fishing communities the quality should be on the increase, the application of the improved quality of HUMAN RESOURCES through three indicators, namely physical quality and health, the quality of intellectual (education and training) and spiritual qualities.This issue became important note for the Government because of the presence of obstacles where the quality of HUMAN RESOURCES more precisely to improve the quality of HUMAN RESOURCES was going to be difficult, therefore, needs to be awareness of the Government and the community. The quality of human resources in realizing better or boost community empowerment which is better then the Government should be in driving, giving information, and facilitate Community fishermen.Key Words : Human Resources Quality Coastal Communities